INDUKSI KALUS KRISAN (Chrysanthemum morifolium Ramat var. Tomohon Kuning) DENGAN 2,4-Dichlorophenoxyacetic Acid (2,4-D) DAN 6-Benzylaminopurine (BAP) PADA KONDISI PENCAHAYAAN BERBEDA - Tia Setiawati; Annisa Nur Arofah; Mohamad Nurzaman (Jurnal Pro-Life, 2020)
This study aims to obtain the optimum concentration of 2,4-D and BAP plant growth regulators (PGRs) to induceChrysanthemum callus in light and dark conditions. The method used is an experimental method in the laboratoryusing a Completely Randomized Design (CRD) with 4 treatment of 2,4-D + BAP concentration combinations. Theculture was incubated under different lighting conditions for 45 days after planting. The parameters observedincluded ctexture and color of callus, other responses produced by explants, size, fresh weight and dry weight ofcallus. Data were analyzed descriptively. The results showed that 4 ppm 2,4-D + 0.5 ppm BAP treatment was thebest combination in inducing Chrysanthemum callus in both light and dark conditions. In bright conditions, mostof the callus were dark green and dark brown with a compact texture, callus size of 1.36 cm, and the highest freshweight and dry weight of callus were 0.62 gram and 0.17 gram respectively. Meanwhile, in the dark conditionsmost of the callus were light green and light brown with a compact texture, callus size 1.18 cm, and the highestfresh weight and dry weight of the callus produced were 0.51 grams and 0.15 grams, respectively. Keywords: Callus, Chrysanthemum morifolium, 2,4-Dichlorophenoxyacetic acid (2,4-D), 6-Benzylaminopurine(BAP)